Temperature Dependence of Uranium and Vanadium Adsorption on Amidoxime‐Based Adsorbents in Natural Seawater. Issue 2 (16th January 2018) - Kuo, Li‐Jung; Gill, Gary A.; Tsouris, Costas; Rao, Linfeng; Pan, Horng‐Bin; Wai, Chien M.; Janke, Christopher J.; Strivens, Jonathan E.; Wood, Jordana R.; Schlafer, Nicholas; D'Alessandro, Evan K.
Abstract: Recent advances in the development of amidoxime‐based adsorbents have made it highly promising for seawater uranium extraction. However, there is a great need to understand the influence of temperature on the uranium sequestration performance of the adsorbents in natural seawater. Here the apparent enthalpy and entropy of the sorption of uranium (VI) and vanadium (V) with amidoxime‐based adsorbents were determined in natural seawater tests at 8, 20, and 31 °C that cover a broad range of ambient seawater temperature. The sorption of U was highly endothermic, producing apparent enthalpies of 57 ± 6.0 and 59 ± 11 kJ mol −1 and apparent entropies of 314 ± 21 and 320 ± 36 J K −1 mol −1, respectively, for two adsorbent formulations. In contrast, the sorption of V showed a much smaller temperature sensitivity, producing apparent enthalpies of 6.1 ± 5.9 and −11 ± 5.7 kJ mol −1 and apparent entropies of 164 ± 20 and 103 ± 19 J K −1 mol −1, respectively. This new thermodynamic information suggests that amidoxime‐based adsorbents will deliver significantly increased U adsorption capacities and improved selectivity in warmer waters. A separate field study of seawater uranium adsorption conducted in a warm seawater site (Miami, FL, USA) confirm the observed strong temperature effect on seawater uranium mining. This strong temperature dependence demonstrates that the warmer the seawater where the amidoxime‐based adsorbents are deployed the greater the yield for seawater uranium extraction. Abstract : Thermodynamic parameters of the sorption of uranium and vanadium with amidoxime‐based adsorbents in true natural seawater system were obtained. Laboratory and field data demonstrate that amidoxime‐based adsorbents exhibit greatly increased uranium adsorption capacity and selectivity in warmer seawater.